Attention deficit hyperactivity disorder and other disruptive behavior disorders are risk factors for recurrent epistaxis in children: A prospective case-controlled study - Özgür, Erdoğan; Aksu, Hatice; Gürbüz-Özgür, Börte; Başak, Hatice Sema; Eskiizmir, Görkem (The Turkish Journal of Pediatrics, 2016)
The aim of this study was to investigate the frequency of attention deficit hyperactivity disorder (ADHD) and other disruptive behavior disorders in children with recurrent epistaxis (RE). Children aged between 6-11 years were enrolled according to presence (n=34) and absence (n=103) of RE. Turgay DSM-IV-Based Child and Adolescent Disruptive Behavior Disorders Screening and Rating Scale was applied to parents. Moreover, Schedule for Affective Disorders and Schizophrenia for School-Age Children Present and Lifetime Version was performed. Oppositional defiant disorder (ODD) and ADHD were determined in 17.6% and 32.4% of patients, respectively. When psychiatric diagnoses between both groups were compared, statistically significant differences were found in terms of ADHD and ODD (p=0.028 and p=0.003). In children with RE, the frequency of ADHD and ODD are higher than children without RE. A referral to a child psychiatrist should be considered, if a child with RE also has symptoms of increased activity, inattention and/or body-injurious behaviors.